Analisis Kelayakan Usaha Agroindustri Pemindangan Ikan Menggunakan Decision Support System - Universitasari, Pascawati; Sutantio, Raden Alamsyah; Chairina, Raden Roro Lia; Ambarkahi, Ratih Puspitorini Yekti; Nugraheni, Ponti Primastuti Aulia (Jurnal Akuntansi Terapan dan Bisnis, 2025)
This research aims to analyze the company's feasibility condition from non-financial and financial aspects, the results of which can be used as a reference to recommend company development steps. The approach used in this research is Decision Support System. The results of the analysis show that in the legal aspect the company can be said to be feasible because it already has a letter. The production aspect shows the results that the company is in a feasible condition with a high level of feasibility. Marketing Aspects, Management Aspects and Human Resources and Environmental Aspects show the results that the company is in a feasible condition with a moderate level of feasibility.  In financial aspects consisting of quantity BEP analysis of 24,721.13, Sales BEP of 379,515,345.54, BCR of 1.42, Payback Period of 1.58, NPV of 10,064,036,510.68, PI of 12.54, IRR of 59.20 and the overall analysis of financial aspects shows that the company is in a viable condition. Based on the overall analysis of the UMKM version 2.0 Decision Support System (DSS) approach, it shows that CV Genderang Mercusuar Bahari is in a feasible condition to be developed.